It's Not Who You Know, It's How You Think You Know Them: Suicide Exposure and Suicide Bereavement. Issue 1 (1st January 2018) - Cerel, Julie; Sanford, Rebecca L.
ABSTRACT: Suicide is the tenth leading cause of death overall and the second leading cause of death for youth ages fifteen to twenty-four years old (Drapeau and McIntosh 2016). In 2015, 44, 193 people died by suicide in the United States, and 5, 900 of these deaths were youth between the ages of ten and twenty-four (Drapeau and McIntosh 2016). Each one of these deaths leaves behind a range of people who mourn the loss. Historically in the United States, the people left behind were referred to as suicide survivors, although recently the term has changed to suicide loss survivors . In this paper, we aim to describe research on suicide loss survivors, examine how many people are exposed to and affected by suicide, discuss the wide variety of people who are affected by suicide, and identify the ways in which suicide bereavement is unique. We then introduce the reader to the story of John Smith to illustrate the variety of children and adults who are exposed to a suicide in their family or community. The vignette examines the range of responses to suicide death and how responses vary not just on kinship but on the nature and perceptions of the relationship. Finally, the paper also includes clinical implications and considerations for clinicians working with those who have been affected by suicide death.